Tko se to našao u čudnovatim zgodama: Hlapić ili Dikics? - Bockovac, Timea; Plavac, Morana (SlavVaria, 2024)
Who found themselves in strange adventures: Hlapić or Dikics? This year is dedicated to Ivana Brlić-Mažuranić, a renowned storyteller and internationally acclaimed children's writer, and one of the most translated Croatian authors. Born in 1874, her 150th birthday is celebrated this year. Brlić-Mažuranić wrote poetry, essays, diaries, collections of short stories, and poems for children. In 1913, she garnered significant attention from the literary audience with the publication of the children's novel "Čudnovate zgode šegrta Hlapića." Her crowning achievement is considered to be the collection of short stories "Priče iz davnine" (Stories from the Past), published in 1916. This paper explores the author's literary reception in Hungary, with a primary focus on analyzing the translation of verbs in the novel "Čudnovate zgode šegrta Hlapića." The results obtained will contribute to expanding knowledge about the translation techniques of Croatian-Hungarian texts and can be applied to the teaching unit of text processing.